Data structures and algorithms using Python - Necaise, Rance D. (Hoboken, N.J. : John Wiley & Sons, 2011)
'More and more programmers are turning to Python and this book will give them the understanding they need. Necaise introduces the basic array structure and explores the fundamentals of implementing and using multi-dimensional arrays. The underlying mechanisms of many of Python's built-in data structures and constructs are covered. A number of ADTs and applications are discussed as threads throughout the book to allow for multiple implementations as new data structures are introduced. Real-world applications of the various chapter topics are also presented. This gives programmers complete coverage of abstraction and the basic data structures and algorithms in the Python language'--
Includes bibliographical references and index.
Keywords: Python (Computer program language); Algorithms; Data structures (Computer science)